The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1108/jes-12-2015-0241
|View full text |Cite
|
Sign up to set email alerts
|

A reconciliation proposal of demand-driven growth models in open economies

Abstract: Purpose-This paper seeks to contribute to the literature on demand-driven Keynesian growth in open economies by developing a formal model that combines Dixon and Thirlwall's (1975) export-led growth model and Thirlwall's (1979) balance-of-payments constrained growth models into a more general specification. Then, based on the model developed in this paper, we analyse more broadly some important issues concerning the net impact of currency depreciation on the short-run growth. Design/methodology/approach-We bui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(34 citation statements)
references
References 18 publications
0
34
0
Order By: Relevance
“…In fact, some of the recent work of Professor McCombieespecially the 'grand synthesis' model of Ribeiro et al (2017a) may be interpreted as consistent with such a view. This model does not imply that countries always grow at the long-run, Thirlwall's law growth rate over any given historical period.…”
Section: Rethinking the Balance-of-payments Constraint And More Powerful Empirical Testsmentioning
confidence: 75%
See 2 more Smart Citations
“…In fact, some of the recent work of Professor McCombieespecially the 'grand synthesis' model of Ribeiro et al (2017a) may be interpreted as consistent with such a view. This model does not imply that countries always grow at the long-run, Thirlwall's law growth rate over any given historical period.…”
Section: Rethinking the Balance-of-payments Constraint And More Powerful Empirical Testsmentioning
confidence: 75%
“…Blecker and Ibarra (2013) combined the latter two into final goods. For an alternative way of incorporating intermediate imports into a BPCG model, see Ribeiro et al (2017a;2017b).…”
Section: Empirical Evidence For the Us And Mexican Economiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Building upon Dixon and Thirlwall’s (1975) export-led growth model and Thirlwall’s (1979) balance-of-payments constrained growth model, Ribeiro et al (2017) found that the net impact of currency devaluation on growth can go either way, depending on some structural conditions such as the average share of imported intermediate inputs in prime costs of domestic firms and the institutional capacity of trade unions to set nominal wages through the bargaining process. They also showed that the effectiveness of a competitive real exchange rate to promote growth is higher in countries where the share of labor in domestic income is also higher.…”
Section: Selected Review Of the Literaturementioning
confidence: 99%
“…Growth is a concept that is widely used in various philosophies of science and has various meanings as the process of improvement. In economics, the term growth is associated with the process of development, expansion and acceleration (Akalpler, 2018; Chen, 2018), while, in business terms, growth is interpreted as an increase in economic or business capacity in terms of producing/selling products or services (Pradhan, 2017; Ribeiro, 2017;Saripalli, 2017). Therefore, growth is used in business enterprises as an indicator of success, such as the rate of economic growth or revenue growth rate.…”
Section: Introductionmentioning
confidence: 99%